PENGETAHUAN, SIKAP, DAN PERILAKU MASYARAKAT TENTANG MALARIA DI KABUPATEN OGAN KOMERING ULU DAN LAHAT - Yahya Yahya; Santoso Santoso; Milana Salim (Poltekkes Kemenkes Jambi, 2022)
Background: The results of the regional commitment stipulate that malaria elimination in the Asia Pacific region is expected to be achieved in 2030. Until 2020 there are still several malaria endemic districts in the Province of South Sumatra. This research was conducted to determine the knowledge, attitudes, and behavior of the community in supporting the malaria elimination program in Lahat and Ogan Komering Ulu (OKU) districts. Method: Respondents were selected by purposive sampling method on residents living around ponds that have the potential to become breeding grounds for malaria vector mosquitoes. The population in this study were all residents living in Padang Bindu Village, OKU District and Merapi Village, Lahat District. Interviews were conducted using a semi-open structured questionnaire. Results: The results of this study showed that the proportion of respondents in Merapi Village (40%) has a higher level of good knowledge than Padang Bindu Village (16.7%). Respondents who had a good attitude towards malaria prevention were higher in Lahat District than respondents in OKU. The actions of the people in OKU Regency were mostly those who took good actions (43.3%), while in Merapi Regency there were more people who took bad actions (46.7%) Conclusion: The level of knowledge and attitude of the people of Lahat Regency is better than that of the people of OKU Regency, while the actions of the people of OKU Regency in preventing malaria are better than the people of Lahat Regency.